The reliability and validity of the Affinity Altitude hypoxic generators in acute and chronic conditions - Willmott, A. G. B.; Chung, H. C.; Roberts, J. D.; Maxwell, N. S. (Sports Engineering, 2024)
This study investigated the reliability of the Affinity Altitude hypoxic generator within-day, between-day and between-generator under acute and chronic hypoxic conditions. An additional objective was to assess the validity of the fraction of inspired oxygen (FiO2) values in relation to the claimed manufacture`s reference values to ensure the accuracy and safety of the product. Three altitude generators (Affinity Altitude Ltd., Sussex, UK) were assessed across all available settings during a test-retest design for equivalent FiO2 and output volume. This consisted of two phases: 1) acute exposure (10 min per setting) and 2) chronic exposure (8 h per setting). FiO2 and volume data were calculated from 1 min collection samples using the Douglas bag method for acute and chronic exposures. There were low variations in FiO2 data across all settings within the acute exposure for within-day (coefficient of variation [CV] range: 0.0-2.6%), between-day (0.2-1.3%), and between-generator analysis (0.7-1.4%). This was similarly found for volume data within-day (0.1-3.7%), between-day (0.7-5.4%), and between-generator (1.2-3.0%). Equally, for chronic exposure trials, CV for FiO2 (< 4.0%) and volume (< 5.0%) across each of the generators presented low variations. The FiO2 values were similar to reference values, however, significant differences were found for settings 4 (-0.3% [17.6% vs. 17.9% reference value]) and 5 (-0.1% [15.8% vs. 15.9% reference value], both p < 0.05). A `good` level of reliability (CV < 5%) and validity were found within and between the Affinity Altitude`s generators. However, a review of the reference values is warranted, and long-term experimental studies are required to determine the efficacy of this device for the purpose of physiological adaptations. 1 Introduction